Fabrication of graphene-based flexible supercapacitors in planar- and fiber-structured configurations - Abdul Bashid, Hamra Assyaima (2019)
With the emergence of flexible electronic devices, flexible supercapacitors have attracted widespread interest in developing lightweight, thin and efficient portable/wearable energy storage devices. Along with the general information about flexible supercapacitors, this thesis focuses on flexible supercapacitors including the planar-structured flexible supercapacitors as well as the new-type fiber supercapacitors. Thus, in this thesis, the construction of electroactive materials on the flexible substrates and feasible strategies to achieve highperformance flexible supercapacitors were discussed. In the planar-structured flexible supercapacitors, aluminium carbide was being employed as a current collector, where it is light, thin and highly flexible. The simultaneous exfoliation and reduction of graphene-based materials by rapid microwave irradiation were employed to generate a microwave graphene mix (MGM). To demonstrate the supercapacitors application, a supercapacitor device were constructed and yielded a specific capacitance value of 78.1 F g-1 using a solid-state electrolyte with excellent cycling stability of 93.8% after 1000 cycles of charge/discharge. Then, the as-prepared MGM was mixed with polypyrrole (PPy) to further enhance the electrochemical performance. A supercapacitor device using MGM-PPy as an electroactive material recorded a specific capacitance value of 137.2 F g-1 which is 1.8 times higher than that of MGM with cycling stability of 89.9% after 1000 cycles of charge/discharge. Different from the planar-structured supercapacitors, the fiber-structured was fabricated through a simple electrochemical deposition process of polypyrrole/reduced graphene oxide onto the surface of carbon bundle fiber. The surface morphology revealed a high degree of porosity in the PPy-rGO-2 composite; facilitating the ionic penetration, leading to an excellent electrochemical performance. The PPy-rGO-2 exhibits good electrochemical performance (96.2 F g-1) with an energy density of 13.4 Wh kg-1 and a power density of 322.9 W kg-1. However, after a series of charging-discharging cycles, the electrochemical performances of the PPy-rGO-2 deteriorated due to the changes in the structural properties such as the reduction in pore size, and transformation of the structure of rGO from amorphous to graphitic. To investigate the mechanical bendability/flexibility of the as-fabricated supercapacitor devices, both planar- and fiber-structured supercapacitor devices were bent at various angles and revealed that the bending had nearly no effect on the specific capacitance values. The combination of solid-state electrolyte and flexible current collector with flexible free-standing electroactive materials made up of graphene-based materials and PPy, capable of withstanding stress with no drastic changes in its electrochemical performance, demonstrating an excellent mechanical bendability. Overall, the sustainable electrochemical performance, mechanical flexibility, low-cost and lightweight, flexible supercapacitors are undoubtedly emerging as promising renewable energy technology for future energy storage systems.